The ROSA project: leveraging e-learning to a semantic layer. (27th February 2007) - Porto, Fabio; De Carvalho Moura, Ana Maria; Coutinho Da Silva, Fabio Jose; Pereira Fernandez, Adriana
Learning Content Management System (LCMS) supports e-learning applications with storage and efficient access for e-Learning Objects (LOs). In order to foster LCMS adoption by the e-learning community, an important issue is to bring course modelling to the realm of the LCMS. In this paper, we describe the Repository of Objects with Semantic Access (ROSA) project. ROSA is a LCMS that provides users with a conceptual map view of courses. We present ROSA data model designed as an extension to RDF data model with ordered collections, relationship properties and cardinality constraints. An algebra is proposed with operations supporting queries over LO metadata and navigation through conceptual maps. Relationship properties are implicitly considered during navigation. User queries can be expressed through a high-level query language, directed by a browsing interface or based on keyword search over LO attribute values. Additionally, a thesaurus is used during query processing extending the domain vocabulary with synonyms, generic/specific and Associated Terms (ATs). Furthermore, ROSA supports the contextualisation of conceptual maps through an extension based on Topic Maps (TM). Finally, the system provides users with a computable semantic layer representation of conceptual maps, which includes course modelling and course material management, leveraging current LCMS.